Capital structure and practices of accrual-based earnings management among non-financial Vietnamese listed firms - Pham Duc Hieu; Hoang Ha Anh (Investment Management & Financial Innovations)
This paper’s primary goal is to examine the influence of a firm’s capital structures on practices of accrual-based earnings management by doing empirical research covering 51 non-financial Vietnamese listed companies during a period from 2013 to 2022. To estimate accrual-based earnings management practices, the modified Dechow and Dichev (2002) model was mobilized. Then, a regression between earnings management estimated values based on accruals and a group of capital structure variables and control variables that are hypothesized to influence earnings management practices is performed. The feasible generalized least square model is used to address econometric issues. Empirical results reveal that activities for managing accrual-based earnings indicate a considerable adverse influence from institutional ownership. However, other hypothesized variables that are management ownership, ownership concentration, foreign ownership, and leverage do not have a determinant sign as expected. ROA, one of five control factors, has a favorable impact on accrual-based earnings management practices, whereas company size has a negative impact. The study provides useful information to investors and stakeholders for their making investment decisions in Vietnam. The empirical findings are also based for recommendations to control earnings management practices at Vietnamese listed enterprises to enhance accounting information quality, thus contributing to the sustainable development of the Vietnam Stock Exchange.